Myeloid related protein 8 and 14 secretion reflects phagocyte activation and correlates with disease activity in juvenile idiopathic arthritis treated with autologous stem cell transplantation. Issue 3 (1st March 2003) - Wulffraat, N M; Haas, P J; Frosch, M; de Kleer, I M; Vogl, T; Brinkman, D M C; Quartier, P; Roth, J; Kuis, W
Abstract : Objectives: To determine whether myeloid related proteins (MRP8/MRP14), a complex of two S100 proteins related to neutrophil and monocyte activation, might be used as a marker for disease activity, and as an early indicator of relapse in juvenile idiopathic arthritis. Patients and methods: A group of 12 patients who underwent an autologous haematopoietic stem cell transplantation (ASCT) for refractory juvenile idiopathic arthritis (JIA) were studied. MRP8/MRP14 serum concentrations were determined by a sandwich enzyme linked immunosorbent assay (ELISA) as described. Improvement from baseline was described by a definition of improvement employing a core set of criteria as detailed previously by Giannini. Results: After ASCT, MRP8/MRP14 serum concentrations in JIA showed a positive correlation with the Child Health Assessment Questionnaire (CHAQ; r =0.80) and erythrocyte sedimentation rate ( r =0.45), but not with the total leucocyte count ( r =0.26). Mean MRP8/MRP14 serum concentrations dropped markedly in the first three months after ASCT (p=0.0039) and clinical parameters of disease activity such as CHAQ markedly improved (p=0.0039). During a transient relapse there was an increase in MRP8/MRP14. Conclusions: MRP8/MRP14 serum concentration can be used as a marker for disease activity in patients who receive an ASCT for refractory JIA. This indicates a role of macrophage activation in the pathogenesis of JIA. The occurrence of MAS in three patients in this study was not preceded by significant changes in MRP8/MRP14 concentration.